Serum glycan markers for evaluation of disease activity and prediction of clinical course in patients with ulcerative colitis. - Koji Miyahara; Kazuhiro Nouso; Shunsuke Saito; Sakiko Hiraoka; Keita Harada; Sakuma Takahashi; Yuki Morimoto; Sayo Kobayashi; Fusao Ikeda; Yasuhiro Miyake; Hidenori Shiraha; Akinobu Takaki; et al. (PLoS ONE, 2013)
BACKGROUND: The aims of this study were to determine the change of whole-serum N-glycan profile in ulcerative colitis (UC) patients and to investigate its clinical utility. METHODS: We collected serum from 75 UC patients at the time of admission and the same number of age/sex-matched healthy volunteers. Serum glycan profile was measured by comprehensive quantitative high-throughput glycome analysis and was compared with disease activity and prognosis. RESULTS: Out of 61 glycans detected, 24 were differentially expressed in UC patients. Pathway analysis demonstrated that highly sialylated multi-branched glycans and agalactosyl bi-antennary glycans were elevated in UC patients; in addition, the glycan ratio m/z 2378/1914, which also increased in UC, showed the highest Area under Receiver Operating Characteristic curve (0.923) for the diagnosis of UC. Highly sialylated multi-branched glycans and the glycan ratio m/z 2378/1914 were higher in the patients with total colitis, Clinical Activity Index >10, Mayo endoscopic score 3, or a steroid-refractory status. In particular, the glycan ratio m/z 2378/1914 (above median) was an independent prognostic factor for the need for an operation (hazard ratio, 2.67; 95% confidence interval, 1.04-7.84). CONCLUSIONS: Whole-serum glycan profiles revealed that the glycan ratio m/z 2378/1914 and highly sialylated multi-branched glycans increase in UC patients, and are correlated with disease activity. The glycan ratio m/z 2378/1914 was an independent predictive factor of the prognosis of UC.